Alignment of Rutaceae Genomes Reveals Lower Genome Fractionation Level Than Eudicot Genomes Affected by Extra Polyploidization - Yuan, Jiaqing; Wang, Jinpeng; Yu, Jigao; Meng, Fanbo; Zhao, Yuhao; Li, Jing; Sun, Pengchuan; Sun, Sangrong; Zhang, Zhikang; Liu, Chao; Wei, Chendan; Guo, He; et al. (Frontiers in Plant Science, 2019)
Owing to their nutritional and commercial values, the genomes of several citrus plants have been sequenced, and the genome of one close relative in the Rutaceae family, atalantia (Atalantia buxifolia), has also been sequenced. Here, we show a family-level comparative analysis of Rutaceae genomes. By using grape as the outgroup and checking cross-genome gene collinearity, we systematically performed a hierarchical and event-related alignment of Rutaceae genomes, and produced a gene list defining homologous regions due to ancestral polyploidization or speciation. We characterized genome fractionation resulting from gene loss or relocation, and found that erosion of gene collinearity could largely be described by a geometric distribution. Moreover, we found that well assembled Rutaceae genomes retained significantly more genes (65-82%) than other eudicots affected by recursive polyploidization. Additionally, we showed divergent evolutionary rates among Rutaceae plants, with sweet orange evolving faster than others, and by performing evolutionary rate correction, re-dated major evolutionary events during their evolution. We deduced that the divergence between the Rutaceae family and grape occurred about 81.15-91.74 million years ago (mya), while the split between citrus and atalantia plants occurred less than 10 mya. In addition, we showed polyploidization led to a copy number expansion of key gene families contributing to the biosynthesis of vitamin C. Overall, the present effort provides an important comparative genomics resource and lays a foundation to understand the evolution and functional innovation of Rutaceae genomes.